Pengaruh Program Fisioterapi terhadap Pemulihan dan Pencegahan Cedera pada Pengguna Gym dan Fitness - Marliana Marliana; Marido Bisra (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
This study aims to evaluate the impact of physiotherapy programs on injury recovery and prevention among gym and fitness users. Injuries caused by intensive physical activities in the gym can hinder training progress and reduce quality of life. Physiotherapy, as a rehabilitation method, offers benefits such as accelerating recovery, reducing pain, improving mobility, and preventing recurring injuries. This research employed an experimental method with a pre-test and post-test design, involving 30 participants who experienced injuries. The participants were divided into two groups: the intervention group, which underwent a physiotherapy program for 6 weeks, and the control group, which did not receive any intervention. The results showed that the intervention group experienced significant improvements in recovery parameters, including reduced pain, increased range of motion, and muscle strength (p < 0.05). These findings confirm that physiotherapy programs are effective in supporting injury recovery while preventing future injuries. This study is expected to serve as a reference for coaches and healthcare practitioners in designing more effective rehabilitation programs for gym and fitness users.